2020
DOI: 10.3847/2041-8213/aba1f3
|View full text |Cite
|
Sign up to set email alerts
|

Eruption of Solar Magnetic Flux Ropes Caused by Flux Feeding

Abstract: Large-scale solar eruptions are believed to have a magnetic flux rope as the core structure. However, it remains elusive as to how the flux rope builds up and what triggers its eruption. Recent observations found that a prominence erupted following multiple episodes of "flux feeding". During each episode, a chromospheric fibril rose and merged with the prominence lying above. In this letter, we carried out 2.5-dimensional magnetohydrodynamic (MHD) numerical simulations to investigate whether the flux-feeding m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…We note that the same conclusion was drawn by Patsourakos et al (2013) from the investigation of another hot channel observed continuously between a CME and its preceding confined eruption. Flux rope formation by reconnection in the corona has been suggested by a number of recent investigations, but several of them did not clearly establish the association with a confined flare (Liu et al 2010;Zhang et al 2014Zhang et al , 2020James et al 2017;Yan et al 2018;Gou et al 2019). Even more recently (while this paper was being revised), several authors pointed out the role of confined flares in forming or significantly enhancing a flux rope prior to a CME (Liu et al 2018;Wang et al 2019;Nindos et al 2020;James et al 2020).…”
Section: A General Picture Of Flux Rope Formation By Confined Eruptionsmentioning
confidence: 84%
“…We note that the same conclusion was drawn by Patsourakos et al (2013) from the investigation of another hot channel observed continuously between a CME and its preceding confined eruption. Flux rope formation by reconnection in the corona has been suggested by a number of recent investigations, but several of them did not clearly establish the association with a confined flare (Liu et al 2010;Zhang et al 2014Zhang et al , 2020James et al 2017;Yan et al 2018;Gou et al 2019). Even more recently (while this paper was being revised), several authors pointed out the role of confined flares in forming or significantly enhancing a flux rope prior to a CME (Liu et al 2018;Wang et al 2019;Nindos et al 2020;James et al 2020).…”
Section: A General Picture Of Flux Rope Formation By Confined Eruptionsmentioning
confidence: 84%
“…In our simulation, the quantities at the lower boundary are fixed, indicating that it corresponds to the photosphere; increment equivalent extrapolation is used at the other boundaries (e.g., Zhang et al 2020):…”
Section: Simulating Proceduresmentioning
confidence: 99%
“…variable method (e.g., Zhang et al 2020) to construct the partially open bipolar background field, which can be cast in the complex variable form…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since there lacks accurate measurement of the local conditions in the corona, the physical essence of flux feeding mechanism is unclear based on observational results alone. To solve this, Zhang et al (2020) (hereafter Paper I) carried out numerical simulations to investigate the scenario of the flux feeding mechanism in BPS configurations. In their simulations, the rising chromospheric fibril is represented by a small flux rope emerging from below a pre-existing coronal magnetic flux rope with a BPS configuration.…”
Section: Introductionmentioning
confidence: 99%